KOMPETENSI GURU SD IT ADZKIA PADANG - Hendrizal Hendrizal; Sisri Wahyuni; Evi Desmariani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Abstract Positive Professional attitude of teacher can make them perform various teachers activities vigorously, otherwise negative professional attitude of teachers tend to reduce their performance. Professional teachers have the competencies required to perform the educational and teaching task appropriately and effectively. Teachers have four basic competencies, pedagogical competence, professional competence, social competence and personal competence. The purpose of this study was to describe the teachers competency of SDIT Adzkia. This type of research is descriptive analysis, a research method that is intended to describe the phenomenon. The population used in this research is all elementary school teachers in SDIT Adzkia Padang, while the sample used is five teachers in SD IT Adzkia Padang. The sampling technique used is random sampling. Based on the results, from the four competency standards that were being observed and the results of questionnaires, the competence of IT Adzkia primary school teachers generally good. Keywords: Competence